2006
DOI: 10.1265/ehpm.11.184
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors and Perceptions of Japanese Tourists Affecting Diarrheal Illness and Health Care Need Assessment: A Questionnaire Study

Abstract: Objectives: To measure the prevalence rate of, and determine the association between food and drink related behaviors and diarrheal illness among Japanese tourists, and assess their health care needs.Methods: Eligible Japanese tourists (1,480) aged ≥15 years traveling in Chiangmai Province in the north, Ayutthaya Province in the center, Kanchanaburi Province in the west, Pattaya City in the east, and Krabi Province in the south of Thailand were enrolled in the study. Of these tourists, 1,318 consented to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…This finding was higher than that from the previous study which was 13.8% [8]. However, it was lower than the findings in some studies among foreign travelers visiting Thailand (21.3%) [9] and Bali (25.5%) [10].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This finding was higher than that from the previous study which was 13.8% [8]. However, it was lower than the findings in some studies among foreign travelers visiting Thailand (21.3%) [9] and Bali (25.5%) [10].…”
Section: Discussioncontrasting
confidence: 81%
“…Length of stay is one the risk factor of TD [14]. The longer the duration of stay, the greater the risk of developing TD compared to shorter duration because long period of stay in a high risk destination can increase the risk of consuming contaminated food and beverages which caused TD [9,15]. On the other hand, this study found that the longer travelers stay at a destination, the greater the likelihood that they acquire natural immunity against enteropathogen [22].…”
Section: Advances In Health Sciences Research Volume 24mentioning
confidence: 93%